Agricultura biológica em Portugal : a importância da utilização de ferramentas de business intelligence na integração e visualização de dados - Costa, Francisco Pereira Gomes Fausto da (2019)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence